2019
DOI: 10.3390/ani9030116
|View full text |Cite
|
Sign up to set email alerts
|

Insect Oil as An Alternative to Palm Oil and Poultry Fat in Broiler Chicken Nutrition

Abstract: This study was conducted to evaluate the effects of Tenebrio molitor (TM) oil as a total replacement for palm oil and poultry fat in broiler chicken diets on growth performance, nutrient digestibility, pancreatic enzyme activity, selected blood parameters and the lipid fatty acid compositions of liver and breast muscle tissues. A total of 72 seven-day-old female Ross 308 broiler chickens were used. The birds were randomly distributed into three groups with 12 replicates each, using two birds per replicate for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 56 publications
4
44
1
2
Order By: Relevance
“…[8] research results obtained higher feed conversion, namely 2.07 -2.16, in rations containing bay leaf flour (Syzgium polyanthum) for five weeks of maintenance. While the results of this study are lower than the study of [14] in which the ration was given ethanol extract up to 3 g / kg of ration, 2.03 to 2.07 with the same basal feed. The difference in ration conversion is caused by the composition of the ingredients used which is different, the feed additives derived from added leaf flour are also different, so that they contain different active substances, thus impacting on the growth and consumption of the ration which in turn results in different ration conversions.…”
Section: Feed Conversioncontrasting
confidence: 80%
“…[8] research results obtained higher feed conversion, namely 2.07 -2.16, in rations containing bay leaf flour (Syzgium polyanthum) for five weeks of maintenance. While the results of this study are lower than the study of [14] in which the ration was given ethanol extract up to 3 g / kg of ration, 2.03 to 2.07 with the same basal feed. The difference in ration conversion is caused by the composition of the ingredients used which is different, the feed additives derived from added leaf flour are also different, so that they contain different active substances, thus impacting on the growth and consumption of the ration which in turn results in different ration conversions.…”
Section: Feed Conversioncontrasting
confidence: 80%
“…The omega 6 to omega 3 fatty acids ratio is one of the wellknown factors to assess healthy diets. The n6/n3 ratio in T. molitor lipids was reported to be very high due to the low levels of the n3 fatty acids (Ravzanaadii et al, 2012;Tzompa-Sosa et al, 2014;Paul et al, 2016;Benzertiha et al, 2019a). It is reported that the addition of omega 3 fatty acids to the feeding substrates will reflect in an increase of these fatty acids in the lipids of T. molitor , Ruschioni et al, 2020.…”
Section: Insect Lipids: An Overviewmentioning
confidence: 99%
“…It has been shown that insects can modulate the intestinal microbiota with positive effects on poultry growth, health, and resistance against pathogens [15][16][17][18][19]. Lipids are a main component of insects (30%-40% of the dry matter, DM) [20] and, once extracted during the insect larvae processing, they can be used as an interesting feed ingredient in animal farming [14,15,[21][22][23][24][25][26] Black soldier fly (Hermetia illucens, HI) and yellow mealworm (Tenebrio molitor, TM) fats are characterized by a different fatty acid (FA) profile. The HI fat is rich in saturated FAs (SFAs) and in MCFAs, mainly lauric acid (C12:0; 48% of the total FA profile) [14], which has an antimicrobial effect on a wide range of microbes [27].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that insects can modulate the intestinal microbiota with positive effects on poultry growth, health, and resistance against pathogens [ 15 , 16 , 17 , 18 , 19 ]. Lipids are a main component of insects (30%–40% of the dry matter, DM) [ 20 ] and, once extracted during the insect larvae processing, they can be used as an interesting feed ingredient in animal farming [ 14 , 15 , 21 , 22 , 23 , 24 , 25 , 26 ]…”
Section: Introductionmentioning
confidence: 99%